Ontological model development work process / Prof. Madya Dr. Haryani Haron … [et al.] - Haron, Prof Madya Dr Haryani; Md Sabri, Sabiroh; Mohd Radzi, Muhammad Hamiz; Basaruddin, Suzana (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Indigenous Knowledge (IK) has known to be long exist and used by the local people in certain environments in making their living. This knowledge are vital and crucial for the sustainability and the existence of a society and therefore need to be preserved from extinction. For this purpose, a work process to develop an ontological model is crucial to preserve Indigenous Knowledge (IK), a knowledge which is tacit, scattered and unorganized hence could easily become extinct. Currently, most knowledge organization model are static and difficult to be managed in a dynamic environment. Therefore, we develop a dynamic and comprehensive ontological model through a hybrid method which combining taxonomy and Semantic web technology. The combined features of ontological model and Semantic web technology provide a more balanced solution for ontology mapping and information structuring thus assist users in retrieving information easily. The dynamic characteristic of the ontology caters the rapid evolution of knowledge in a domain. The development of the ontological model for IK could be used as a reference point by many organizations towards nurturing a knowledge society which is important to our socio-economy. Organizations could also use it for decision making as well as venturing into new and diversification of business opportunities. In the future, the ontological model development work process could be replicated for other domain's use particularly for knowledge preservation